Green Financing as a Tool to Mitigate Climate Change for Sustainable Development: An Insight form Egypt - Elsherif, Marwa (International Journal of Economics and Financial Issues, 2023)
Climate change is undoubtedly one of the long-term challenges confronting humanity across the globe. Most of the economies have taken serious initiatives that support reduce greenhouse gas emissions as well as accelerate financial flows to clean and sustainable projects. This study investigates the influence of green financing on environmental sustainability – represented by climate change mitigation- in Egypt from 1990 to 2021. Augmented Dickey–Fuller (ADF), Phillip-Peron (PP) unit root tests and Quantile Autoregressive Distribute Lag (QARDL) Model were employed for empirical estimates. Results reveal that green financing is negatively associated with greenhouse gas emissions. It is also worth noting that research and development (R&D) investment promotes environmental sustainability, while population growth hinders it. Moreover, economic growth does not play a vital role in climate change. There are still many fences to green finance that need to be addressed. It is recommended that policymakers push the financial sector to adopt a green finance strategy to further the goals of long-term sustainable development.